Do ethnobotanical and laboratory data predict clinical safety and efficacy of anti-malarial plants? - Willcox, M; Benoit-Vical, F; Fowler, D; Bourdy, G; Burford, G; Giani, S; Graziose, R; Houghton, P; Randrianarivelojosia, M; Rasoanaivo, P (BioMed Central, 2011)
BACKGROUND: Over 1200 plant species are reported in ethnobotanical studies for the treatment of malaria and fevers, so it is important to prioritize plants for further development of anti-malarials. METHODS: The "RITAM score" was designed to combine information from systematic literature searches of published ethnobotanical studies and laboratory pharmacological studies of efficacy and safety, in order to prioritize plants for further research. It was evaluated by correlating it with the results of clinical trials. RESULTS AND DISCUSSION: The laboratory efficacy score correlated with clinical parasite clearance (rs=0.7). The ethnobotanical component correlated weakly with clinical symptom clearance but not with parasite clearance. The safety component was difficult to validate as all plants entering clinical trials were generally considered safe, so there was no clinical data on toxic plants. CONCLUSION: The RITAM score (especially the efficacy and safety components) can be used as part of the selection process for prioritising plants for further research as anti-malarial drug candidates. The validation in this study was limited by the very small number of available clinical studies, and the heterogeneity of patients included.